Development of an immunoassay for the detection of mycotoxins using xMAP technology and its evaluation in black tea samples - Ishrat Jahan Saifi
Mycotoxins, a natural food contaminant, are secondary metabolites of fungi. Aflatoxin B1 (AFB1) and ochratoxin A (OTA) are two major mycotoxins found in various food commodities. These mycotoxins are hepatotoxic, nephrotoxic, cytotoxic, mutagenic and carcinogenic, thus they are a public health concern and their monitoring in food commodities is necessary. There are several conventional techniques available for mycotoxin detection, such as HPLC, LCMS, and ELISA. However, extensive nature and huge cost allowances make it challenging to deploy these techniques for monitoring of mycotoxins in the large sample size. Therefore, a robust, responsive and high-throughput technique is required. Here, we aimed to develop a multiplexed Luminex suspension assay based on multi analyte profiling (xMAP) technology for the simultaneous detection of AFB1 and OTA in the black tea, which is found to be contaminated with these mycotoxins during the cultivation or processing steps. Limit of detection for AFB1 and OTA, was 0.06 ng/ml and 0.49 ng/ml, respectively without any cross-reactivity with other mycotoxins and this assay is suitable for simultaneous detection of AFB1 and OTA in the same sample. Collectively, based on the results, we suggest that the developed Luminex suspension assay is sensitive, accurate, rapid and suitable for high-throughput screening of multiple mycotoxins.